PROFITABILITAS, HARGA SAHAM DAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Wisnu Haryo Pramudya; Slamet Herutono; Ani Sri Murwani Kumala Kapti (Accounting Global Journal, 2022)
This study aims to test whether profitability has an effect on stock prices and test whether firm size has an effect on profitability on stock prices. This study uses the independent variable profitability with ROA as a proxy, the dependent variable is stock price and firm size as moderating variables. In this study, the hypothesis proposed is to prove the significance of the effect of profitability on stock prices, and firm size has an effect on the effect of profitability on stock prices. Moderated Regression Analysis is an analytical tool used to analyze the proposed hypothesis, because basically MRA is designed to determine the relationship between two variables that are influenced by the moderator variable, this is a regression equation where there is an interaction between the multiplication of two or more independent variables. The population used is all contractor and real estate companies listed on the IDX for the 2018-2020 period. The method used to take the sample is purposive sampling. The results of this study prove that all hypotheses built can be accepted.